The effect of salidroside in promoting endogenous neural regeneration after cerebral ischemia/reperfusion involves notch signaling pathway and neurotrophic factors - Jiabing Zheng; Jizhou Zhang; Jing Han; Zhichang Zhao; Kan Lin (BMC Complementary Medicine and Therapies, 2024)
Abstract Background Salidroside is the major bioactive and pharmacological active substance in Rhodiola rosea L. It has been reported to have neuroprotective effects on cerebral ischemia/reperfusion (I/R). However, whether salidroside can enhance neural regeneration after cerebral I/R is still unknown. This study investigated the effects of salidroside on the endogenous neural regeneration after cerebral I/R and the related mechanism. Methods Focal cerebral I/R was induced in rats by transient middle cerebral artery occlusion/reperfusion (MCAO/R). The rats were intraperitoneally treated salidroside once daily for 7 consecutive days. Neurobehavioral assessments were performed at 3 days and 7 days after the injury. TTC staining was performed to assess cerebral infarct volume. To evaluate the survival of neurons, immunohistochemical staining of Neuronal Nuclei (NeuN) in the ischemic hemisphere were conducted. Also, immunofluorescence double or triple staining of the biomarkers of proliferating neural progenitor cells in Subventricular Zone (SVZ) and striatum of the ischemia hemisphere were performed to investigate the neurogenesis. Furthermore, reverse transcription-polymerase chain reaction (RT-PCR) and enzyme-linked immunosorbent assay (ELISA) were used to detect the expression of neurotrophic factors (NTFs) brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF). Expression of Notch1 and its target molecular Hes1 were also analyzed by western-blotting and RT-PCR. Results Salidroside treatment ameliorated I/R induced neurobehavioral impairment, and reduced infarct volume. Salidroside also restored NeuN positive cells loss after I/R injury. Cerebral I/R injury significantly increased the expression of 5-Bromo-2’-Deoxyuridine (BrdU) and doublecotin (DCX), elevated the number of BrdU/Nestin/DCX triple-labeled cells in SVZ, and BrdU/Nestin/glial fibrillary acidic protein (GFAP) triple-labeled cells in striatum. Salidroside treatment further promoted the proliferation of BrdU/DCX labeled neuroblasts and BrdU/Nestin/GFAP labeled reactive astrocytes. Furthermore, salidroside elevated the mRNA expression and protein concentration of BDNF and NGF in ischemia periphery area, as well. Mechanistically, salidroside elevated Notch1/Hes1 mRNA expression in SVZ. The protein levels of them were also increased after salidroside administration. Conclusions Salidroside enhances the endogenous neural regeneration after cerebral I/R. The mechanism of the effect may involve the regulation of BDNF/NGF and Notch signaling pathway.